ONE-DIMENSIONAL SYSTEMS - Tursunova Maftuna Sulton qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: One-dimensional (1D) systems represent a fundamental concept in physics and materials science, particularly in the study of condensed matter and nanotechnology. This article explores the theoretical foundations, experimental models, and emerging applications of one-dimensional systems. It includes a literature analysis of key developments, reviews methodological approaches for simulating and studying these systems, and discusses experimental results with implications for quantum transport, optical properties, and device engineering. The study highlights the significance of 1D systems in modern physics and proposes future directions in research and application.